Nematodes : alternatives to chemical control - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Reference: 'Principles and Practice of Nematode Control in Crops', edited by R.H. Brown, Plant Research Institute Department of Agriculture and Rural Affairs, Burnley Gardens, Burnley, AUSTRALIA and: B.R. Kelly, Nematology Department, Rothamsted Experimen